Targeted Mutagenesis of Burkholderia thailandensis and Burkholderia pseudomallei through Natural Transformation of PCR Fragments - Thongdee, Metawee (American Society for Microbiology (ASM), 2008)
Burkholderia pseudomallei is the causative agent of melioidosis, an overwhelming, rapidly fatal septic infection, and B. thailandensis is a closely related, less virulent species. Both organisms are naturally competent for DNA transformation, and this report describes a procedure exploiting this property for the rapid generation of marked deletion mutations by using PCR products. The method was employed to create 61 mutant strains. Several selectable elements were employed, including elements carrying loxP and FRT recombinase recognition sites to facilitate resistance marker excision. Chromosomal mutations could also be transferred readily between strains by transformation. The availability of simple procedures for creating defined chromosomal mutations and moving them between strains should facilitate genetic analysis of virulence and other traits of these two Burkholderia species.